Respecting Adherents of Other Religions: Common Words in Ashoka Vedic and Islamic Teaching - Yahya, Yuangga Kurnia; Rachmawati, Fadhillah; Riezma, Ihda (Hanifiya: Jurnal Studi Agama-Agama, 2022)
Truth claims between adherents of religion often make it a basis for disrespecting other faiths and not giving their rights somewhat, as the example conflict in Tanjung Balai, North Sumatra on 2016, Sri Lanka in 2018, and Rohingya. This article highlights the common word between Buddhism and Islam in respecting adherents of other religions by taking the object of the Ashoka Inscription in Buddha and the verses of the al-Qur’an and Sunnah, which discuss the rights of followers of other religions. This study uses the ‘Kalimatun Sawa’ theory (a common word). This research shows that Ashoka's life history shows the application of Buddhism in social life, including in respecting adherents of other religions as they respect their religion. Islam teaches that insulting adherents of other religions is a form of insulting Allah. These religious teachings place the same respect for followers of other religions as respecting their religions. This concept is the basis for dialogue between the two religions and is a meeting point for building peace between religious communities.